Perlindungan Hukum Para Pihak Dalam Perjanjian Jual Beli Melalui Media Elektronik Dengan Sistem Cash on Delivery - suryati; Ferryani Krisnawati; Mahardina Pradnya Paramita (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
The aim of this research is to examine and analyze legal protection for parties in sales and purchase agreements via electronic media with a cash on delivery system. To achieve this goal, the approach method used is normative juridical. The data source is secondary data as the main data, which consists of primary legal materials, secondary legal materials and tertiary legal materials. The data obtained was then analyzed qualitatively. Conclusion: legal protection for parties in electronic sales and purchase agreements with a cash on delivery system is carried out in a preventive and repressive manner. Preventive legal protection is carried out by carrying out obligations by the parties which will be able to prevent disputes or defaults as regulated in the Civil Code, Law Number 8 of 1999 concerning Consumer Protection, Government Regulation Number 80 of 2019 concerning Trading via Electronic Systems, Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, and Government Regulation Number 71 of 2016 concerning 2019 concerning Implementation of Electronic Systems and Transactions. Repressive legal protection can be provided by parties by filing a lawsuit against the party who caused the loss through litigation or non-litigation.